Reproductive Tract Infection In A Village Area Of Bangladesh (KYAMC Journal, 2017)
Objective: To asses the incidence of reproductive tract infection among the married women in the reproductive age group living in the rural area of Bangladesh.Study design: Retrospective studyMethod: Hospital based study done for a period of six month January 2013 to june 2013. Only married women suffering from reproductive tract infection were included.Result: Out of 1288 female patient attended for treatment in OPD, 582 (46.47%) were found affected by RTI. Women of age between 15-35 years were mostly affected (85%). Abnormal vaginal discharge (100%) and itching were the most common symptoms. The disease was more common among the illiterate women (72%) and in low socio-economic group (58%).KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 642-644